Exploring Students’ Challenges and Strategies in Academic Writing: A Qualitative Study on the Talent Scouting Program - Zaki, Nazbudin; Miftachudin, Miftachudin (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
The purpose of this research is to understand the students’ challenges and strategies when they are joining academic writing class on talent scouting program batch 2022 of UIN Salatiga. This research employs descriptive qualitative research model by involving 25 students who joined talent scouting program batch 2022 of UIN Salatiga. The instruments used questionnaire and interviews in order to obtain the data. The data were analyzed and interpreted through qualitative procedure. The research finds that the students face challenges; lack of vocabularies, grammar mastery, choosing correct words, motivation, and presenting clear idea. Writing weakness and negative environment are also part of the issues. The findings also showed the students’ strategies to confront those challenges such as the social strategies, memory strategy, compensatory strategies, metacognitive strategies, cognitive strategy, and affective strategies. From the result, it can be concluded that students from different majors joining the academic writing class were struggled to learn and meet the requirement of academic writing, so they are advised to allocate more time in self-regulated learning outside of the classes. Keywords: Academic writing, Challenges, Strategies.